P104 Anaeroplasma, a potential anti-inflammatory probiotic for the treatment of chronic intestinal inflammation. (March 2019) - Beller, A; Kruglov, A; Durek, P; von Goetze, V; Hoffmann, U; Maier, R; Heiking, K; Siegmund, B; Heinz, GA; Mashreghi, M-F; Radbruch, A; Chang, H-D
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: The human intestine is colonized with billions of microorganisms, which form the gut microbiota, consisting of up to 1000 different bacterial species. Recent studies have implicated the intestinal microbiota in the pathogenesis of chronic inflammatory diseases, such as rheumatoid arthritis, systemic lupus erythematosus, ankylosing spondylitis, systemic sclerosis, and Sjögren's syndrome. Yet, we still lack the knowledge which bacteria of the gut microbiota induce, promote or inhibit chronic inflammatory inflammation. Objectives: The aim of our work is to identify members of the intestinal microbiota with pro- or anti-inflammatory properties for targeted and therapeutic manipulation of the microbiota in chronic inflammatory diseases. Methods: We have developed high-resolution microbiota flow cytometry which allows us to analyze the microbiota on a single cell level. This provides a non-invasive, fast and efficient diagnostic tool to visualize dramatic changes of microbiota composition in inflammatory diseases, fast and efficiently, and isolate distinct bacteria for functional and molecular analyses. Results: We have identified bacteria belonging to the genus Anaeroplasma, which enhances the levels of mucosal IgA. Adoptive transfer of Anaeroplasma increases the numbers of IgA+ germinal center B cells in the Peyer's patches and of IgA-secreting plasma cells in the lamina propria of the small intestine leading to significantly enhanced mucosal IgA levels. Anaeroplasma controls IgA expression presumably its ability to induce expression of the regulatory cytokine TGF-β in T cells, as we show here. Conclusions: The anti-inflammatory properties of Anaeroplasma to induce the anti-inflammatory cytokine TGF-β, thereby also strengthening the intestinal barrier by enhancing mucosal IgA, qualify Anaeroplasma as potent probiotic for the prevention and treatment of chronic inflammation. Disclosure of Interest: None declared.